2013
DOI: 10.1016/j.juro.2013.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Secondary Surgery After Hypospadias Repair: A Population Based Analysis of 5,000 Patients

Abstract: This population based study produced significantly different results than small studies of select patients and techniques. Distal hypospadias repair is associated with a 9% secondary surgery rate. Low surgeon volume independently increases the risk of fistula, stricture or diverticulum repair. Increased patient age at primary distal hypospadias repair increases the risk of cystoscopy and urethral dilation/incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 9 publications
4
31
0
4
Order By: Relevance
“…2 treatment of hypospadias remains surgical, and multiple surgeries, especial ly for more severe forms of hypospadias, are often required to achieve functional and cosmetically acceptable outcomes. 3 Patients with severe hypospadias are at risk of complications leading to lifelong difficulties with urination and sexual function, and an increased risk of psychological problems. thus, hypospadias is an important health issue, which can be a substantial burden on health-care resources.…”
Section: Introductionmentioning
confidence: 99%
“…2 treatment of hypospadias remains surgical, and multiple surgeries, especial ly for more severe forms of hypospadias, are often required to achieve functional and cosmetically acceptable outcomes. 3 Patients with severe hypospadias are at risk of complications leading to lifelong difficulties with urination and sexual function, and an increased risk of psychological problems. thus, hypospadias is an important health issue, which can be a substantial burden on health-care resources.…”
Section: Introductionmentioning
confidence: 99%
“…The "acceptable" complication rate is historically based upon expert opinion [7][8] and the EAU current recommendation to benchmark complications below 10% is based upon level 2b evidence 9 , but this is not specific to the type of complication. Revision surgery for a complex proximal urethrocutaneous fistula is wholly different to that for mild meatal stenosis.…”
mentioning
confidence: 99%
“…21,22 Previous studies have shown that centres that operate on more than 20 cases per year have a better operative success than those that operate less frequently, 21 and surgeons who perform 20 primary repairs annually have reduced odds of failure compared with those who perform 10 per year. 23 Although the minimum number of hypospadias repairs per year a surgeon must perform to be considered competent remains debatable, it is recommended that hypospadias repairs be performed by surgeons who perform a high volume of repairs and are intellectually interested in this subject, with continuous review of their own results. 17 The current three-member team in our institution strikes a balance between surgical outcomes and other practical issues, such as stable staffing, expertise, training, and succession.…”
Section: Discussionmentioning
confidence: 99%